Rice intensification in Bangladesh improves economic and environmental welfare. Issue 95 (May 2019) - Shew, Aaron M.; Durand-Morat, Alvaro; Putman, Ben; Nalley, Lawton L.; Ghosh, Aniruddha
Highlights: Rice consumption in Bangladesh increased by 12.6% as a result of HYV production. HYV rice in Bangladesh contributes an additional 26 million rations per capita annually. HYV rice provides increased food security with less environmental impacts. Abstract: Sustainable agricultural intensification (SAI) practices can help meet current and future food security needs while decreasing environmental impacts. To date, no studies have simultaneously estimated the food security and environmental implications of previously adopted rice intensification regimes. Thus, our study analyzes the food security and environmental impacts associated with two major rice intensification practices in Bangladesh: (1) planting rice in multiple seasons and (2) replacing traditional (TYV) rice with High Yielding Varieties (HYV). Bangladeshi rice production data by growing season and variety were gathered for 2012–2015 from the Bangladesh Bureau of Statistics and farm management information were collected from the Bangladeshi Livelihood Systems survey. A partial equilibrium trade model of the global rice economy was implemented to estimate trade impacts, price effects, and producer and consumer welfare changes from rice instensification. Additionally, a Life Cycle Assessment (LCA) was used to estimate the environmental impacts of both intensified and traditional rice systems. The results indicate a 12.60% increase in Bangladeshi consumption associated with historical HYV rice adoption, which equates to enough additional rice for nearly 26 million people annually. Moreover, the LCA results suggest that HYV was more input and water use efficient per kg of rice produced even with increased inputs per ha in at least one season, and in no case was TYV more efficient. Global Warming Potential associated with rice systems was substantially less across all seasons in HYV compared to TYV per kg of rice produced. These results demonstrate the importance of promoting improved seed technology adoption and multiple rice seasons as key pathways for addressing food insecurity and reducing environmental impacts from agriculture.